Antidiabetic and Hypolipidemic Effects of Extracts of Gymnema Sylvestre in Streptozotocin Induced Type I Diabetes in Rats - Mahida, Nishtha R.; Mandali, G.C.; Sindha, Vijaysinh V.; Raval, S.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Gymnema sylvestre of the family Asclepiadaceae is one of the most important medicinal plants of the central eco-region. It is popularly known as Gurmar, which means “sugar killer”. Extract of leaves is reported to have tannins, gum, flavonoids, proteins and saponins. It has displayed a wide array of pharmacological activities. This study was aimed to investigate the antidiabetic and hypolipidemic effects of Gymnema sylvestre extract in experimentally induced diabetes in rats. Diabetes was produced in adult Wistar rats with single dose of streptozotocin (STZ) @ 60 mg/kg b.wt. intraperitoneally. After the confirmation of diabetes on 7th day (sugar >200 mg/dl), alcoholic and aqueous extracts of G. sylvestre (400 mg/kg) were administered orally to the experimental rats from 8th day and continued for 42 days thereafter. The antidiabetic and hypolipidemic activity was estimated by measuring blood glucose, lipid profile and histopathological examination of various tissues from all the groups. Administration of STZ resulted in a significant (p<0.01) increase in blood glucose and lipid profile and histopathological alterations in Diabetic control group as compared to healthy control group. Gymnema treatment demonstrated significant (p<0.01) antidiabetic effect indicated by restoration of blood glucose compared to STZ control group. The study concluded that extracts of Gymnema sylvestre improved the altered glucose and lipid profile in diabetic rats, suggesting that the Gymnema Sylvestre extracts exhibit the antidiabetic and hypolipidemic activity.